The Effect Of Training, Work Discipline And Work Environment On Employee Performance At PT Laundry Box In Batam City: - Sadipun , Maria Mariana; Sanga , Laurensius Dihe; Harianja , Josephin (Tractare: Jurnal Ekonomi-Manajemen, 2024)
This research was conducted using quantitative research methods with a total population of 60 respondents. Sampling using saturated sampling technique in which all populations are used as samples. Data collection techniques used questionnaires and distributed via google forms. Data analysis used SPSS version 26. The research results found that the job training variable has value -2,814 < 1,671 with a significance value of 0.007 > 0.05, then was rejected and was accepted, the work discipline variable has a value 5,232 > 1,671 with a significance value of 0.000 > 0.05, then was accepted and was rejected, the work environment variable has a value 2,522 > 1,671 with a significance value of 0.015 > 0.05, then was accepted and was rejected. The three variables, namely training, work discipline and work environment, have 18,298 > 2,77 with a significance value of 0.000 > 0.05, This shows that simultaneously training, work discipline and work environment have a positive and significant effect on the performance of employees of PT Laundry Box in Batam City.